Ligand‐Promoted Cooperative Electrochemical Oxidation of Bio‐Alcohol on Distorted Cobalt Hydroxides for Bio‐Hydrogen Extraction. Issue 12 (13th May 2021) - Deng, Chen; Wu, Kuang‐Hsu; Lu, Xinxin; Cheong, Soshan; Tilley, Richard D.; Chiang, Chao‐Lung; Lin, Yu‐Chang; Lin, Yan‐Gu; Yan, Wensheng; Scott, Jason; Amal, Rose; Wang, Da‐Wei
Abstract: Hydrogen is increasingly viewed as a game‐changer in the clean energy sector. Renewable hydrogen production from water is industrialized by integrating water electrolysis and renewable electricity, but the current cost of water‐born hydrogen remains high though. An ideal scenario would be to produce value‐added chemicals along with hydrogen so the cost can be partially offset. Herein, facilitated bio‐hydrogen extraction and biomass‐derived chemical formation from sugar‐derived 5‐hydroxymethyfurfural (HMF) were achieved via the in‐situ transformation of cobalt‐bound electrocatalysts. The cyanide‐bound cobalt hydroxide exhibited a low voltage at 1.55 V at 10 mA cm −2 for bio‐hydrogen production, compared with an iridium catalyst (1.75 V). The interaction between the biomass intermediate and the cyanide ligand is suggested to be responsible for the improved activity. Abstract : Green hydrogen : Cyanide‐bound cobalt hydroxides in‐situ grown from Prussian blue analogue Co3 [Co(CN)6 ]2 in alkaline solution deliver excellent activity with low anodic onset potential for biomass oxidation. The excellent performance is attributed to the cyanide group and adjacent unsaturated Co sites cooperatively promoting the biomass oxidation with associated cyanide stabilization.